Analysis of Income Level and Labor Absorption in The Furniture Industry in Dana Urban Village Watopute Sub-District Muna Regency - Sumadi, Arni; Dirgantoro, Muhammad Arief; Sadimantara, Fahria Nadiryati (Department of Agribusiness, Halu Oleo University, 2021)
This research is the background of the problems which the village this is one of the areas which most populated eyed living as a handyman wood. Industrial furniture is considered a role in providing fieldwork and increasing the income of society that is in the environment that will but on years 2017 to 2019, the industry of furniture in the Village of Dana have experienced a decline in the industry. The research aims to determine the amount of revenue in the furniture industry in the Dana Village Watopute Sub-District Muna District and determine the amount of absorption labour in the furniture industry in the Dana Village Watopute Sub Muna District. The number of samples in research is 35 people, while the methods used in the study are the analysis of revenues and analysis of the absorption labour. The study showed that the magnitude of the average income by businessman industrial furniture in the Dana Village amounted to about IDR 7.781.808. the level of income that is the lowest of IDR 2.985.287 and revenues was the highest of IDR 17.185.843, the amount of labour working in the industry of furniture in the Dana village in the year 2018 to 2020 experienced a decline. In the year 2020, the absorption of workers works at 6,14 percent.